2022
DOI: 10.1093/ijnp/pyac062
|View full text |Cite
|
Sign up to set email alerts
|

Role of Orbitofrontal Cortex and Differential Effects of Acute and Chronic Stress on Motor Impulsivity Measured With 1-Choice Serial Reaction Time Test in Male Rats

Abstract: Background Deficits in motor impulsivity, i.e. the inability to inhibit a prepotent response, are frequently observed in psychiatric conditions. Several studies suggest that stress often correlates with higher impulsivity. Among the brain areas affected by stress, the orbitofrontal cortex (OFC) is notable because of its role in impulse control. OFC subregions with unique afferent and efferent circuitry play distinct roles in impulse control, yet it is not clear what OFC subregions are engaged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…This is the first study to investigate differences in brain metabolism using [ 18 F]FDG and PET imaging in high vs. low impulsive rats. We observed that RHA rats exhibited lower [ 18 F]FDG uptake in brain regions that have been associated with impulsive behaviors, such as the mPFC 26,44 , NAc 19 , OFC 45 and thalamus 46 . This is consistent with clinical data showing lower cortical glucose metabolism in patients with ADHD 47 or borderline personality disorders [48][49][50] , who also display low impulse control 51 .…”
Section: Discussionmentioning
confidence: 86%
“…This is the first study to investigate differences in brain metabolism using [ 18 F]FDG and PET imaging in high vs. low impulsive rats. We observed that RHA rats exhibited lower [ 18 F]FDG uptake in brain regions that have been associated with impulsive behaviors, such as the mPFC 26,44 , NAc 19 , OFC 45 and thalamus 46 . This is consistent with clinical data showing lower cortical glucose metabolism in patients with ADHD 47 or borderline personality disorders [48][49][50] , who also display low impulse control 51 .…”
Section: Discussionmentioning
confidence: 86%
“…Treatment with the α2 adrenergic antagonist and pharmacological stressor yohimbine impairs “waiting”, as indexed by increased premature responses on the 5-CSRTT ( Adams et al, 2017 ; Baek et al, 2017 ; Barlow et al, 2018 ; Broos et al, 2017 ; Chernoff et al, 2021 ; Sun et al, 2010 ) and higher response rates on a DRL task ( Sanger, 1988 ), both of which reduced opportunities to obtain rewards. Similarly, cold stress also increases DRL responding ( Thomas et al, 1991 ), and inescapable shock stress increases premature response on a 1-CSRTT ( Girotti et al, 2022 ). These previous findings, in combination with the present data suggest that in males, acute stress impairs response inhibition in a variety of circumstances, where premature responses may either delay reward delivery or result in more explicit punishments.…”
Section: Discussionmentioning
confidence: 99%